A review of the Kawerau Geothermal Field, New Zealand. (January 2016) - Milicich, S.D.; Clark, J.P.; Wong, C.; Askari, M.
Highlights: Kawerau Geothermal Field is a multi-user geothermal development. Geothermal drilling began in 1951, with now >70 wells drilled for various purposes. Stratigraphy comprises basement greywacke and volcano-sedimentary sequence. Deep hot fluid moves from south to north through faults and fractures. Paper describes current knowledge of the geology, geophysics and fluid chemistry. Abstract: Drawing on earlier work of scientists and engineers, along with results from recent drilling, this paper describes the current knowledge of the geology, geophysics and fluid chemistry of the Kawerau Geothermal Field. The historical and recent data have been evaluated and integrated to present a consistent hydrogeological model of the field. The field extends over an area of 22 km 2, with a natural surface to near-surface heat flow of 100–150 MWt (thermal) (Bromley, 2002 ). Drilling began at Kawerau in 1951 to supply steam to the Tasman pulp and paper processing plant and for power generation, with continued drilling since this time resulting in more than 70 wells being drilled. There is currently ∼121 MWe (electrical) generation commissioned at Kawerau. Deep hot water (>300 °C), sourced in the south, moves across and flows north into the field, through faults and fractures in otherwise impermeable basement greywacke into the overlying volcano-sedimentary sequence. The hot fluids spread laterally into permeable zones along sub-horizontal volcanic and sedimentary layers, with lacustrine sediments, and welded intervals within some ignimbrite units, acting as localised aquitards.